Vertebral column decortication for the management of sharp angular spinal deformity in Pott disease: Case report. Issue 45 (November 2017) - Hu, Hong-Tao; Liu, Feng-Yu; Yu, Jin-He; Ren, Liang; Gu, Zhen-Fang; Sun, Xian-Ze
Abstract: Rationale: Extremely sharp angular spinal deformity of healed tuberculosis can be corrected by vertebral column resection (VCR). However, the VCR techniques have many limitations including spinal column instability, greater blood loss, and greater risk of neurologic deficit. Patient concerns: We described a new spinal osteotomy technique to collect sharp angular spinal deformity in Pott disease. A 52-year-old woman presented with back pain and gait imbalance. Diagnosis: The kyphosis of healed tuberculosis was diagnosed based on history and imaging examinations. Intervention: A new posterior VCR was designed to treat this disease. Outcomes: The neurological function improved from Japanese Orthopedic Association scale 3 to 7. The back pain and neurological function were significantly improved. The Oswestry Disability Index decreased from 92 to 34. There was also a significant decrease in back pain visual analog scale from 9 to 2. Lessons: For cases with extremely severe Pott kyphotic deformity, the technology of modified VCR offers excellent clinical and radiographic results.